Barriers to treatment among young adults living with a substance use disorder : findings from working with the community-oriented substance use program in Tshwane, South Africa - Visser, M.J. (Maretha Johanna) (University of Pretoria, 2023)
Thesis (PhD (Psychology))--University of Pretoria, 2023.